Judicial Interpretation of Strict Liability in Environmental Law a Comparison Between Indonesia and China - Mikhael Wijaya; Ida Nurlinda; Dadang Epi Sukarsa (Law Development Journal, 2026)
Strict liability principle allows legal accountability for environmental pollution without requiring proof of fault. This article aim to compares its application in Indonesia and China through a normative-legal and comparative approach. In Indonesia, the principle is regulated under Article 88 of Law No. 32 of 2009 concerning Environmental Protection and Management, yet its implementation remains inconsistent due to the absence of technical regulations and institutional weaknesses. In contrast, China applies strict liability more effectively through environmental courts, reversed burden of proof, and public interest litigation by prosecutors. These differences indicate the urgency of strengthening enforcement instruments in Indonesia so that the principle can function as an operational tool for environmental protection. The proposed policy recommendations include drafting implementing regulations, establishing environmental courts, and reforming procedures for public lawsuit.